Pulmonary valve neocuspidisation with glutaraldehyde‐treated autologous pericardium—A novel technique in pulmonary valve endocarditis. Issue 7 (24th June 2020) - Kumar, Rupesh; Halder, Vikram; Gourav, Krishna P.; Patel, Ruchit; Munirathimnam, Ganesh K.; Mandal, Banashree; Thingnam, Shyam K. S.
Abstract: Infective endocarditis (IE) is a serious condition leading to heart failure, persistent sepsis. The management of IE involving valve is mainly excision of the infected valve and replacement with a heart valve; which are also at the risk of prosthetic valve endocarditis. Hence repair of the valve with autologous pericardium is much more physiological. We had a 20‐year‐old male presented with features of heart failure and high‐grade fever not responding to optimum medical management. Two‐dimensional echocardiogram revealed vegetation on pulmonary valve cusps with the erosion of the left and right cusps. Neo cusps with autologous pericardium offered good hemodynamics with trivial regurgitation. The patient is doing well with normal pulmonary valve function 3 months after surgery. This technique is reliable, economic, and easily reproducible.